2000
DOI: 10.1093/ps/79.10.1424
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of mortality in specific-pathogen-free layer chickens by a caprine serum fraction after infection with Pasteurella multocida

Abstract: Caprine serum was fractionated by size, and its proteinaceous material <8,000 Da [caprine serum fraction immunomodulator 2 (CSF-I2)] was evaluated for its ability to impart immunoresistance to specific-pathogen-free (SPF) layer chickens. The SPF layers were challenged with 18 to 30 cfu of Pasteurella multocida X-73 (serotype 1) at 5 wk of age. A high degree of mortality was apparent 24 and 48 h later (62+/-14% and 88+/-7%, respectively). Mortality observed after 48 h was minimal. Noting the rapid onset of mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Caprine serum was fractionated to isolate its complement of peptides. An isolate containing three peptides, tripeptidic immunostimulant (TPI), proved to have no bactericidal activity but significantly improved the rate of survival of chickens infected with Pasteurella multocida (9). In this study, we developed a model to help characterize the prophylactic benefit of the TPI preparation in mice.…”
mentioning
confidence: 99%
“…Caprine serum was fractionated to isolate its complement of peptides. An isolate containing three peptides, tripeptidic immunostimulant (TPI), proved to have no bactericidal activity but significantly improved the rate of survival of chickens infected with Pasteurella multocida (9). In this study, we developed a model to help characterize the prophylactic benefit of the TPI preparation in mice.…”
mentioning
confidence: 99%
“…The basis for this conclusion is that asialo-GM1 depletes more than 95% of the NK cell activity. Even though some antigen activated CD4þ and CD8þ T-cells could also be depleted by anti-asialo-GM1 in addition to NK cells [Slifka et al, 2000], IIRF had previously been shown to have no effect on CD4þ/CD8þ T-cell levels [Willeford et al, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with IIRF demonstrated an ability to protect against lethal bacterial challenges such as Salmonella typhimurium [Parker et al, 2002] and Pasteurella multocida [Willeford et al, 2000]. IIRF was most effective when given 24 h prior to challenge.…”
Section: Nk Cells Mediate An Iirf-induced Immune Response Against Bacmentioning
confidence: 93%
See 1 more Smart Citation
“…Defensins could easily be concentrated during the ammonium sulfate fractionation procedure used to manufacture CSF-I. Caprine serum and the large (≥10 kDa) and small (≤10 kDa) molecular weight material fractionated from it by size filtration were screened for bactericidal activity against a series of Gram-positive and Gram-negative bacteria including S. typhimurium using disk agar diffusion assays [Willeford et al, 2000]. Bactericidal activity was not found in any of these products and therefore it is logical to conclude that CSF-I did not promote its prophylactic benefit through a typical defensin-like action.…”
Section: Discussionmentioning
confidence: 99%